Method of construction spatial transition curve - Ustenko, S. A.; Didanov, S. V. (Science and Transport Progress, 2013)
Purpose. The movement of rail transport (speed rolling stock, traffic safety, etc.) is largely dependent on the quality of the track. In this case, a special role is the transition curve, which ensures smooth insertion of the transition from linear to circular section of road. The article deals with modeling of spatial transition curve based on the parabolic distribution of the curvature and torsion. This is a continuation of research conducted by the authors regarding the spatial modeling of curved contours. Methodology. Construction of the spatial transition curve is numerical methods for solving nonlinear integral equations, where the initial data are taken coordinate the starting and ending points of the curve of the future, and the inclination of the tangent and the deviation of the curve from the tangent plane at these points. System solutions for the numerical method are the partial derivatives of the equations of the unknown parameters of the law of change of torsion and length of the transition curve. Findings. The parametric equations of the spatial transition curve are calculated by finding the unknown coefficients of the parabolic distribution of the curvature and torsion, as well as the spatial length of the transition curve. Originality. A method for constructing the spatial transition curve is devised, and based on this software geometric modeling spatial transition curves of railway track with specified deviations of the curve from the tangent plane. Practical value. The resulting curve can be applied in any sector of the economy, where it is necessary to ensure a smooth transition from linear to circular section of the curved space bypass. An example is the transition curve in the construction of the railway line, road, pipe, profile, flat section of the working blades of the turbine and compressor, the ship, plane, car, etc.